2018
DOI: 10.1016/j.ihj.2018.01.032
|View full text |Cite
|
Sign up to set email alerts
|

The predictors of no reflow phenomenon after percutaneous coronary intervention in patients with ST elevation myocardial infarction: A meta-analysis

Abstract: ObjectiveTo investigate the no reflow risk factors after percutaneous coronary intervention in ST elevation myocardial infarction patients.MethodSample size, mean ± standard deviation (SD) or frequencies (percent) of normal and no reflow groups were extracted from each study.ResultsOf 27 retrospective and prospective studies, we found that increasing risks of no reflow were associated with advanced age, male, family history of coronary artery disease, smoking, diabetes mellitus, hypertension, delayed reperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
2
23

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 99 publications
(191 reference statements)
10
78
2
23
Order By: Relevance
“…Several reports have shown that multivessel disease is frequently associated with no-reflow phenomenon (31). In the current study, there were no differences with respect to the ratio of multivessel disease between no-reflow and reflow groups.…”
Section: Discussioncontrasting
confidence: 54%
“…Several reports have shown that multivessel disease is frequently associated with no-reflow phenomenon (31). In the current study, there were no differences with respect to the ratio of multivessel disease between no-reflow and reflow groups.…”
Section: Discussioncontrasting
confidence: 54%
“…При виникненні транзиторної оклюзії коронарної артерії з подальшим відновленням кровопостачання може виникнути патологічний стан, при якому відновлення кровотоку по інфаркт-залежній артерії (ІЗА) не супроводжується відновленням адекватної міокардіальної перфузії [4,5]. Ця ситуація отримала назву феномену невідновленого кровотоку (ФНК).…”
Section: вступunclassified
“…Для оцінки ступеня відновлення коронарного кровотоку прийнято орієнтуватися на ангіографічні критерії за шкалою TIMI (Thrombolysis In Myocardial Infarction) (табл. 1) [4][5][6]. Однак критерієм ефективності ТЛТ та ЧКВ має бути не тільки відновлення кровотоку в епікардіальній частині ІЗА (ТІМІ 3), а й повна і стійка реперфузія тканин в ішемізованій ділянці міокарда, що приведе до обмеження зони некрозу [4].…”
Section: оригінальні дослідженняunclassified
“…Така парадоксальна ситуація описана в літературі як slow-reflow та no-reflow phenomenon або феномен невідновленого кровотоку (ФНК) [18], який має багатофакторний характер розвитку і прогресування з послідовним приєднанням основних його складових -ішемії міокарда, реперфузії та атеротромбоемболізму [6,12]. J.K. Fajar [5] у нещодавньому метааналізі 27 проспективних досліджень ФНК, показав, що відсутність оптимальної перфузії міокарда трапляється у 2-40 % випадків реваскуляризації, хоча є повідомлення про те, що частка пацієнтів з оптимальною реперфузією міокарда після ЧКВ становить не більше 35 % [19]. Кілька досліджень показали, що виникнення ФНК має сильний негативний вплив на прогноз, що знижує потенційну користь від ЧКВ [10], тому стратифікація ризику та рання діагностика ФНК можуть допомогти покращити результати лікування пацієнтів з ІМ.…”
Section: оригінальні дослідженняunclassified
See 1 more Smart Citation